Anti-inflammatory Mechanism of Geniposide: Inhibiting the Hyperpermeability of Fibroblast-Like Synoviocytes via the RhoA/p38MAPK/NF-κB/F-Actin Signal Pathway - Deng, Ran; Li, Feng; Wu, Hong; Wang, Wen-yu; Dai, Li; Zhang, Zheng-rong; Fu, Jun (Frontiers in Pharmacology, 2018)
Geniposide (GE) is the extraction and purification of iridoid glycosides from the Gardenia jasminoides Ellis, which is a promising anti-inflammatory drug, but its mechanism of actions on rheumatoid arthritis (RA) has not been clarified. This study investigated the molecular mechanism behind GE reduced the high permeability of fibroblast-like synoviocytes (FLSs) derived from SD rats with adjuvant arthritis (AA), with the aims of observing the action of GE in AA rats and exploring new therapeutic strategies for RA treatment. The CCK-8 method was used to detect FLSs proliferation. The pro-inflammatory cytokines levels and anti-inflammatory cytokines levels in FLSs were determined by ELISA kits. FLSs permeability assay was performed on Transwell. Immunofluorescence was used to assay the arrangement and morphology of F-actin. The expression of the key molecules related to FLSs permeability (RhoA, p-p38MAPK, NF-κB p-p65 and F-actin) was detected by western blotting. After treatment with lipopolysaccharide (LPS), the proliferation and the permeability of the cells increased significantly (all P<0.05). The expression of RhoA, p-p38MAPK, NF-κB p-p65 and F-actin in FLSs was higher compared with the control group, and F-actin was redistributed,with the formation of additional stress fibers. But, these conditions were moderated after treatment with GE. We demonstrated that the treatment of different concentrations of GE (25, 50, 100 μg/mL) had a significant inhibitory effect on the proliferation and permeability of FLSs in vitro. Furthermore, the levels of interleukin (IL)-1β and IL-17 secreted by FLSs were decreased in different doses of GE groups, and the levels of anti-inflammatory cytokines (IL-4, TGF-β1) were increased. Under treatment with GE, low expression of RhoA downregulated expression of p-p38MAPK, NF-κB p-p65 and F-actin while compared with control group, and restored the hyperpermeability of FLSs due to LPS treatment. Taken together, GE might play its anti-inflammatory and immunoregulatory effects via regulating the relative equilibrium of pro-inflammatory cytokines and anti-inflammatory cytokines. GE attenuated the hyperpermeability of FLSs. The down-regulation of the conduction of RhoA/p38MAPK/NF-κB/F-actin signal may play a critical role in the mechanisms of GE on RA. GE could be an effective therapeutic agent for the treatment of RA. Keywords: geniposide; adjuvant arthritis; fibroblast-like synoviocytes; F-actin; perpermeability;